(untitled) (World Bulletin of Education and Learning, 2026)
This article examines the semantic characteristics and functional features of nouns with diminutive-affectionate meaning in modern Russian. Diminutive nouns represent a productive lexical and word-formation category that not only expresses the notion of smallness but also conveys a wide range of emotional, evaluative, and pragmatic meanings. The study analyzes the mechanisms of diminutive formation, their semantic variability, and their communicative functions in different speech contexts. Particular attention is paid to the role of diminutive nouns in expressing the speaker’s attitude, creating emotional expressiveness, and reflecting cultural and linguistic values. The findings demonstrate that diminutive-affectionate nouns constitute an important component of the Russian linguistic worldview and play a significant role in both everyday communication and literary discourse.